2023
DOI: 10.1177/00219983231168698
|View full text |Cite
|
Sign up to set email alerts
|

Low velocity impact behavior of auxetic CFRP composite laminates with in-plane negative Poisson’s ratio

Abstract: Introducing auxeticity or negative Poisson’s ratio is one potential solution to mitigate the low velocity impact damage of fiber reinforced polymer matrix composites, which can be achieved by tailoring the layup of an anisotropic composite laminate. This study aims to investigate the effect of laminate-level in-plane negative Poisson’s ratio on the low velocity impact behavior of carbon fiber reinforced polymer (CFRP) matrix composites using numerical simulations. The layups of the auxetic composites that allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The delamination resistance of the composite was improved by inserting stitching or a Z-pin into the laminate, and this method was used to effectively inhibit the extension of delamination cracks. Lin et al [24] and Wang [25] investigated the effect of a negative Poisson's ratio on the low-velocity impact of carbon fiber composite laminates through numerical simulation. The results showed that the negative Poisson's ratio structure helps reduce the tensile damage of the fibers and matrix and the delamination damage area.…”
Section: Introductionmentioning
confidence: 99%
“…The delamination resistance of the composite was improved by inserting stitching or a Z-pin into the laminate, and this method was used to effectively inhibit the extension of delamination cracks. Lin et al [24] and Wang [25] investigated the effect of a negative Poisson's ratio on the low-velocity impact of carbon fiber composite laminates through numerical simulation. The results showed that the negative Poisson's ratio structure helps reduce the tensile damage of the fibers and matrix and the delamination damage area.…”
Section: Introductionmentioning
confidence: 99%
“…While auxeticity is present in nature under different forms [ 2 ], it is common today to artificially produce cellular structures [ 3 , 4 , 5 , 6 ], foams [ 7 ], composite materials [ 8 , 9 , 10 ], and cellular geometries with globally auxetic behavior; the latter are often called auxetic meta-materials. Among the several cellular meta-materials [ 11 ], auxetic materials have recently attracted a lot of interest in multiple fields of engineering [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that the internal damage was highly dependent on the type and arrangement of the yarns, where the composites with aramid fibers as the warp yarns and carbon fibers as the weft yarns synergistically had the best performance in terms of impact tolerance. Lin et al [ 14 ] and Wang et al [ 15 ] introduced a negative Poisson’s ratio structure to reduce the damage, and the investigation results showed that the fiber and matrix tensile damage of negative Poisson’s ratio structured laminates could be reduced by about 40% under LVI. Moreover, processes such as stitching [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ] and Z-pin [ 23 , 24 , 25 ] could also effectively improve the delamination resistance of composites.…”
Section: Introductionmentioning
confidence: 99%